2008
DOI: 10.1177/003335490812300103
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Poverty as Risk for Disease: Recommendations from CDC's Consultation on Microenterprise as HIV Prevention

Abstract: In March 2006, the Centers for Disease Control and Prevention (CDC) convened a consultation meeting to explore microenterprise as a potential human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) prevention intervention. The impulse to link microenterprise with HIV/AIDS prevention was driven by the fact that poverty is a significant factor contributing to the risk for infection. Because increasingly high rates of HIV infection are occurring among women, particularly among poor African Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 40 publications
(47 reference statements)
3
57
0
Order By: Relevance
“…Social and economic dependence on a male partner has been suggested as a possible target for gender-specific HIV interventions. 33 Exchange of sex is often part of a personal economic strategy for at-risk women, 34 and our findings suggest that an informal exchange of sex for material support exists within the social networks of our cohort. In areas with high rates of poverty, women may seek out multiple partners to get financial support.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Social and economic dependence on a male partner has been suggested as a possible target for gender-specific HIV interventions. 33 Exchange of sex is often part of a personal economic strategy for at-risk women, 34 and our findings suggest that an informal exchange of sex for material support exists within the social networks of our cohort. In areas with high rates of poverty, women may seek out multiple partners to get financial support.…”
Section: Discussionmentioning
confidence: 58%
“…38 Microenterprise encompasses a broad range of activities, including providing financial literacy, basic life-skills training, and development of commercially viable products and services. 34 Sherman et al reported findings from a pilot economic enhancement HIV-prevention study among women drug users involved in the sex trade in Baltimore. 39 This high-risk cohort was taught how to make and sell beaded jewelry.…”
Section: Discussionmentioning
confidence: 99%
“…The study's randomized design, participants' session attendance, and the overall high follow-up rates increase our confidence in the results. Unlike many microenterprise programs that screen for success, participants were not selected on any skills such as literacy or training experience [25]. Rather, we were interested in examining the effects of the intervention on street-based FSWs who were very likely to be illiterate and had minimal experience with any formal training programs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased focus on structural interventions has brought attention to microenterprise programs in the HIV social science literature [9,25]. Microenterprise is a broad term that refers to a range of programs that target individuals who lack access to traditional banking services and the formal labor market.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, microfinance strategies have been underutilised in the USA and pose a potential new direction for HIV prevention research. 25 Such programs can support networks between African American women and nourish the creativity, faith, strength and resiliency that have helped sustain African American women in the face of social inequalities.…”
mentioning
confidence: 99%